The Effectiveness of the Parental Behavior Model Educational Package Based on the Lived Experiences of Parents with Gifted Children on the Cognitive Ability of Pre-school Children with Moderate Intelligence - Khodadadi, Jamileh; Abedi, Ahmad; Malekpour, Mokhtar; Ghamarani, Amir (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study was to investigate the effectiveness of the Parental behavior model educational package based on the lived experiences of parents with gifted children on the cognitive ability of pre-school children with moderate intelligence. Method: The research was applied and the experimental method (experimental and control group) was used. The statistical population consisted of all parents with preschool children and their children in Arak from October 2020 to October 2021. 20 parents and their children (9 girls and 11 boys) were randomly selected from a comprehensive preschool center and were divided into two experimental and control groups. Tehran-Stanford-Bineh intelligence scale was used to measure children’s cognitive ability. Then the parents of the experimental group received 13 training sessions. At the end, the post-test was administered to all students. The data were analyzed using the statistical model of analysis of covariance and with the SPSS (version 26). Results: The findings showed that the educational package had a positive effect on non-verbal intelligence (F=11/85, P<0/05), verbal intelligence (F=9/93, P<0/05), total intelligence (F=14/12, P<0/05), fluid reasoning (F=10/43, P<0/05), knowledge (F=9/33, P<0/05), quantitative reasoning (F=6/38, P<0/05), visual-spatial processing (F=9/70, P<0/05) and working memory (F=9/26, P<0/05). Conclusion: in the golden age, with parent education and enriching the environment, it is possible to had positive effect on the development of children abilities and its positive consequences.